(3JhVjM GdJPcQI (B_ (3aj Yde GdgjFIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s ((3HdO cJGgjI s)
(3ChdgG (B:s
(3hHYO , jbhd (B: (3ef GdeYdhe Cf GdYdhe JJHGjf ai GdTQa HMSH JHGjf ehVhYGJgG hgh Yde gjFI GdCadGc hCf cJGH GdJPcQI ai gPG Gdaf GdefShH Edi GdWhSi Cf CcJH ajg TQMkG jPdd ef GddaX UhGHg s
(3BNQgG (B:s
(3aEf GdCYeGd HGdfjGJ , hHgG JLdH GdHQcGJ , hJfGd GdOQLGJ , hGdMeO ddg deHOY Gdcd hbO EJab aQGZi ef JCdja gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG CTcGd hQShes
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGXs
(3HBNQgG ebGHdI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdadcs